Characteristics of the double-torsion test to determine the R-curve of ceramic materials - de Albuquerque, Maria da Consolação Fonseca [UNESP]; Rodrigues, José de Anchieta (FapUNIFESP (SciELO), 2006)
Double-torsion tests were carried out on a commercial ceramic floor tile to verify whether this test is suitable for determining the R-curve of ceramics. The instantaneous crack length was obtained by means of compliance calibration, and it was found that the experimental compliance underestimates the real crack length. The load vs. displacement curves were also found to drop after maximum loading, causing the stress intensity factor to decline. The R-curves were calculated by two methods: linear elastic fracture mechanics and the energetic method. It was obtained that the average values of crack resistance, R, and the double of the work of fracture, 2 · γwof, did not depend on notch length, a0, which is a highly relevant finding, indicating that these parameters were less dependent on the test specimen's geometry. The proposal was to use small notches, which produce long stable crack propagation paths that in turn are particularly important in the case of coarse microstructures.
Keywords: Double-torsion; Fracture mechanics; R-curve; Coarsening; Crack propagation; Load testing; Tile; Torsion testing; Double-torsion test; Energetic method; Ceramic materials